Global instability by runaway collisions in nuclear stellar clusters: numerical tests of a route for massive black hole formation - Cortés Vergara, Marcelo; Escala, A; Schleicher, Dominik R. G.; Reinoso, Bastián (Monthly notices of the Royal Astronomical Society, 2023)
The centres of galaxies host nuclear stellar clusters, supermassive black holes, or both. The origin of this dichotomy is still a mystery. Nuclear stellar clusters are the densest stellar system in the Universe, so they are ideal places for runaway collisions to occur. Previous studies have proposed the possible existence of a critical mass scale in such clusters, for which the occurrence of collisions becomes very frequent and leads to the formation of a very massive object. While it is difficult to directly probe this scenario with simulations, we here aim for a proof of concept using toy models where the occurrence of such a transition is shown based on simplified compact systems, where the typical evolution time-scales will be faster compared to the real Universe. Indeed our simulations confirm that such a transition takes place and that up to 50 per cent of the cluster mass can go into the formation of a central massive object for clusters that are above the critical mass scale. Our results thus support the proposed new scenario on the basis of idealized simulations. A preliminary analysis of observed nuclear star clusters shows similar trends related to the critical mass as in our simulations. We further discuss the caveats for the application of the proposed scenario in real nuclear star clusters.
Gesehen am 19.08.2023